Examining rural health equity and impact through the translational science benefits model: outcomes from the CTSA Consortium of Rural States (CORES) - Padek, Maggie; Butcher, Rebecca; deLacerda Allen, Rebecca; Surratt, Hilary L.; Subramain, Maran; Tigges, Beth; Eggleston, Alyson G.; Presley, Jessica H.; Matheson, Trent; Sharareh, Nasser (Frontiers in Public Health, 2025)
IntroductionRural communities often lack access to healthcare, have limited resources and infrastructure, and may experience suboptimal translation of evidence-based interventions into practice or measurement of translational research impact. The Consortium of Rural States (CORES), comprising eight Clinical and Translational Science Award (CTSA) hubs, is a research consortium that focuses on clinical and translational research impacting rural health.MethodsUtilizing the Translational Science Benefits Model (TSBM) framework, each CTSA hub’s evaluation lead co-created an inventory of rural-focused activities, projects, and initiatives that occurred at their respective site during the funding period 2021–2023. Variables included program area; activity type and description; target population; activity status; outputs; and short-term outcomes. The evaluators then mapped site outcomes according to the four TSBM domains (clinical, community, economic, policy) and 30 subcategories (benefits).Results184 rural-focused activities, projects and initiatives were identified across the hubs. All rural-focused efforts involved impacts in the Community and Clinical domains of the TSBM, with >60% focusing on Community impacts. These results suggest an opportunity gap to better define Economic and Policy-level impacts in the context of rural-focused initiatives.DiscussionThis work demonstrates a novel mapping of the TSBM to rural health research settings and explores the nuances of using the concepts and domains of the TSBM as a coding tool. This work gives the Consortium insight on the types of projects and impacts that are supported and how to prioritize more exploration of the full range of translational science benefits in rural health initiatives going forward.